2015
DOI: 10.14411/eje.2015.076
|View full text |Cite
|
Sign up to set email alerts
|

Responses of grassland arthropods to various biodiversity-friendly management practices: Is there a compromise?

Abstract: Abstract. The rich species pool in semi-natural grasslands is associated with high spatial and temporal heterogeneity. This empirical study is one of the first to jointly analyze the response of orders, individual species and functional richness of arthropods to particular management practices and to linear landscape features, such as strips of grass and belts of trees. Mostly it was the less mobile, flightless taxa that were negatively affected by immediate disturbance caused by mowing. At a larger time-scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 62 publications
(21 reference statements)
0
21
0
Order By: Relevance
“…These varying responses may be due to the different ways in which natural enemies utilize the habitat and how harvesting impacts those habitat features (Warren, Scifres & Teel 1987;Debinski et al 2011). For example, ground-dwelling predators were generally negatively affected by harvest; similar results were found in other haying studies (Cizek et al 2011;Mazalova et al 2015). Reduced abundances may be due to reduced litter biomass which provides cover, associated prey resources, pupation and nesting habitat for these ground-dwelling arthropods.…”
Section: H a R V E S T E F F E C T S V A R I E D W I T H T A X O N O mentioning
confidence: 61%
“…These varying responses may be due to the different ways in which natural enemies utilize the habitat and how harvesting impacts those habitat features (Warren, Scifres & Teel 1987;Debinski et al 2011). For example, ground-dwelling predators were generally negatively affected by harvest; similar results were found in other haying studies (Cizek et al 2011;Mazalova et al 2015). Reduced abundances may be due to reduced litter biomass which provides cover, associated prey resources, pupation and nesting habitat for these ground-dwelling arthropods.…”
Section: H a R V E S T E F F E C T S V A R I E D W I T H T A X O N O mentioning
confidence: 61%
“…However, the highest carabid diversity was observed for medium management intensity in grasslands managed with different intensities (41). Accordingly, Mazalová et al (42) reported the highest species richness of butterflies and beetles, at a larger time scale, in grasslands mown once a year, especially when applying a combined regime of mowing and grazing. According to Morris (13), Coleoptera in general are more robust to cutting measures than other arthropods (i.e.…”
Section: Nmds (mentioning
confidence: 99%
“…The negative effect of mowing on arthropod biodiversity can be reduced, however, by varying management in space and/or in time (Cizek et al 2012). This can be carried out, for example, by delaying or omitting the first mowing or by leaving uncut refuges (Humbert et al 2012a,b;Buri et al 2013;Mazalová et al 2015).…”
Section: Introductionmentioning
confidence: 99%